Gut microbial functional maturation and succession during human early life. (11th May 2018) - Cerdó, Tomás; Ruiz, Alicia; Acuña, Inmaculada; Jáuregui, Ruy; Jehmlich, Nico; Haange, Sven‐Bastian; von Bergen, Martin; Suárez, Antonio; Campoy, Cristina
Summary: The evolutional trajectory of gut microbial colonization from birth has been shown to prime for health later in life. Here, we combined cultivation‐independent 16S rRNA gene sequencing and metaproteomics to investigate the functional maturation of gut microbiota in faecal samples from full‐term healthy infants collected at 6 and 18 months of age. Phylogenetic analysis of the metaproteomes showed that Bifidobacterium provided the highest number of distinct protein groups. Considerable divergences between taxa abundance and protein phylogeny were observed at all taxonomic ranks. Age had a profound effect on early microbiota where compositional and functional diversity of less dissimilar communities increased with time. Comparisons of the relative abundances of proteins revealed the transition of taxon‐associated saccharolytic and fermentation strategies from milk and mucin‐derived monosaccharide catabolism feeding acetate/propanoate synthesis to complex food‐derived hexoses fuelling butanoate production. Furthermore, co‐occurrence network analysis uncovered two anti‐correlated modules of functional taxa. A low‐connected Bifidobacteriaceae ‐centred guild of facultative anaerobes was succeeded by a rich club of obligate anaerobes densely interconnected around Lachnospiraceae, underpinning their pivotal roles in microbial ecosystem assemblies. Our findings establish a framework to visualize whole microbial community metabolism and ecosystem succession dynamics, proposing opportunities for microbiota‐targeted health‐promoting strategies early in life.